Kajian Terapan Eko-Interior Pada Objek Rancang Bangun Karya Baskoro Tedjo (Studi Kasus: Selasar Sunaryo Art Space di Bandung, Neo Calista Cafe di Bandung, dan Perpustakaan Bung Karno di Blitar) - Ciwendro, Caroline (Institute of Research and Community Outreach - Petra Christian University, 2014)
Sustainable design appears as human effort in responsing the global environmental issues, which covers aspects of ecology as one of the main pillars. Eco-architecture and eco-interior appear as a single bi, therefore the existence of each influences each other. Dr. Ir. Baskoro Tedjo, MSEB. is one of Indonesia's chief architects who has a view of eco-architecture in his works. The problem is still rare to find a design object with the implementation of a holistic eco interiors, especially in Indonesia. This study aims to examine the applied eco-Interior departing from ecological architecture to obtain comparative results of the three selected objects. The research method used is qualitive, using eco-interior’s parameters and aspects according to Kusumarini (2007). The analysis result shows that Baskoro Tedjo has consistency in the space organization, lighting systems, and air system aspects. On other aspects indicate that each object has vary applied focus to each other. The general conclusions can be drawn is the role of design principals and building managers influence the holistic applied eco interior. In particular, interior designer role in application of ecological interior, as a single entity with ecological architecture.